Environmental Law 60 years ago and today - Gonzalez Ballar, Rafael (2026)
Upon reaching its 162nd issue, the Journal of Legal Sciences has been consolidated and presents 33 academic articles related to Environmental Law. This article analyzes each of them through two evolutionary stages, the first covers the period between 1980 and 1999, while the second covers the year 2000 to 2023.